17. USING PATIENT-SPECIFIC 3D PRINTED CUTTING GUIDE IN LIMB SALVAGE SURGERY (Vietnam Journal of Community Medicine, 2024)
Nowaday, limb salvage surgery still plays an important role in the treatment of malignant bone tumors. Wide resection and bone defect reconstruction are two main components of this procedure. In wide resection technique, surgeons ensure not only safe surgical margin but also preserve important structures such as articular surfaces and ligaments for better reconstruction to maximize limb function. However, balancing between two factors is difficult when using "traditional" resection techniques. Orthopedic oncology has begun to use 3D printing technology to create specific patient-specific cutting guide, that can help surgeons archieve resection with negative margins, especially in pelvis and sacrum tumor. In addition, the bone defect is exactly as preoperative planning, facilitating both biological and mechanical reconstruction and reduce blood loss and operating time. In this report, we present a clinical case using patient-specific 3D printed cutting guide and review studies to evaluate the advantages and limitations of this technique.
Keywords: patient-specific 3D printed cutting guide; limb salvage surgery